The Effect of Inventory Turnover and Turnover Current Assets on Economic Profitability At UD. Rambe Sitahuis District Central Tapanuli District - Sulastri Deviana Hutagalung; Safriadi Pohan; Yenni Sofiana Tambunan (Sean Institute, 2024)
The aim of this research is to determine the effect of inventory turnover and current asset turnover on economic profitability at UD. Rambe, Sitahuis District, Central Tapanuli Regency by drawing the hypothesis that there is an influence of inventory turnover and current asset turnover on economic profitability at UD. Rambe, Sitahuis District, Central Tapanuli Regency. The research results show that there is a positive relationship between inventory turnover and economic profitability and current asset turnover and economic profitability at UD. Rambe, Sitahuis District, Central Tapanuli Regency is 0.958 and 0.858 respectively, so that when interpreted on a value scale it can be categorized as very strong. The regression equation obtained is Y = -0.973 + 0.412X + 0.070X2 which shows the influence of inventory turnover and current asset turnover on economic profitability. The t test shows that the hypothesis proposed is rejected as true, where the t count is 2.141 > 3.18245 for inventory turnover and the t count is 0.206 < 3.18245 for current asset turnover, where both ratios have a positive effect on economic profitability which is not significant, which means it is not certain increases by the respective regression coefficient/slop of 0.412 and 0.070 if the inventory turnover and current asset turnover variables are increased by one unit. Meanwhile, the coefficient of determination shows that inventory turnover and current asset turnover only play a role of 92% in UD's economic profitability. Rambe, Sitahuis District, Central Tapanuli Regency and the remaining 8% is influenced by other factors not included in the model.